2014
DOI: 10.3892/mmr.2014.1978
|View full text |Cite
|
Sign up to set email alerts
|

Role of the local bone renin-angiotensin system in steroid-induced osteonecrosis in rabbits

Abstract: The specific pathogenesis of steroid‑induced osteonecrosis (ON) is yet to be elucidated and until recently effective prophylactic therapies have not been available. The local renin‑angiotensin system (RAS) exists in the bone and has an important role in local bone regulation. However, to the best of our knowledge, the interrelation between local bone RAS and steroid‑induced ON is yet to be investigated. In the present study, 45 rabbits were injected with a single intramuscular dose of 20 mg/kg methylprednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Expressions of different RAS components were reported in the skeletal systems in the current investigation in accordance with other reports 2, 39, 40 . The effector member of RAS (AngII) was found highly expressed together with its forming enzyme, ACE, and receptor (AT1R) in femoral bones heads of OVX osteoporotic animals, which comes in harmony with several studies suggesting the induction of osteoporosis via activation of classical RAS pathway (ACE/AngII/AT1R).…”
Section: Discussionsupporting
confidence: 93%
“…Expressions of different RAS components were reported in the skeletal systems in the current investigation in accordance with other reports 2, 39, 40 . The effector member of RAS (AngII) was found highly expressed together with its forming enzyme, ACE, and receptor (AT1R) in femoral bones heads of OVX osteoporotic animals, which comes in harmony with several studies suggesting the induction of osteoporosis via activation of classical RAS pathway (ACE/AngII/AT1R).…”
Section: Discussionsupporting
confidence: 93%
“…Functional studies revealed that Ang II could stimulate the differentiation and activity of osteoclasts in vivo [14] and in vitro [15] and aggravate the loss of bone minerals in rats with osteoporosis induced by estrogen deficiency [14]; furthermore, the AT1R knockout mice showed high bone mass [16]. In addition, we recently demonstrated that the local RAS in bone was involved in age-related osteoporosis of aging mice [17], bone deteriorations of mice with either obstructive nephropathy [18] or type 1 diabetes [19], and others elucidated the involvement of skeletal RAS in the process of fracture healing in a mouse femur fracture model [20] and the steroid-induced osteonecrosis in rabbits [21] as well as the development of postmenopausal osteoporosis in ovariectomized (OVX) animal models [14,22]. Therefore, the emerging evidences demonstrated that the local RAS displays important biological actions in bone tissue.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, in China, 53.5% of patients with severe acute respiratory syndrome who were prescribed GC developed femoral head osteonecrosis, and SINFH comprises approximately half of non‐traumatic femoral head necrosis. However, the pathogenesis of this disease remains controversial and the various theories explaining SINFH pathogenesis are predominantly classified into the osteoporosis theory, the lipid metabolism disorders theory, the vasculopathy theory, the intraosseous hypertension theory, and the GC cytotoxicity theory.…”
Section: Introductionmentioning
confidence: 99%